ANALISIS PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Pada Balai Metrologi Dinperindag Provinsi Jawa Tengah ) (Students' Journal of Economic and Management, 2013)
This study analyzes the problem of how the influence of environmental leadership and work with the mediation of organizational commitment in improving employee performance Dinperindag Metrology Center of Central Java Province. The purpose of  this study was to identify: (a) a positive and significant relationship between leadership to organizational commitment (b) a positive and significant relationship between the work environment to organizational commitment, (c) a positive and significant relationship between leadership to employee performance (d) a positive influence and significant correlation between the work environment for employees kinereja and (e) positive and signifinkan between organizational commitment to employee performance. The study population is employee status as a civil servant (PNS) working on Dinperindag Metrology Center of Central Java province  amounted to 122 people, while the sampling was done by purposive sampling  is the sampling technique using specific criteria. Based on these criteria obtained sample of 99 people and is used as a respondent. The results of hypothesis testing we can know that the leadership has no effect on organizational commitment, work environment positive influence on employee performance, leadership, positive influence on the performance of employees, work environment positive influence on employee performance, organizational commitment does not affect the performance of the employee. Keywords: leadership, work environment, organizational commitment and employee performance